(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The objective of this study was to evaluate the influence of two organic nanofertilizers, Lithovit and Nagro, on in vitro germination, pollen tube elongation and pollen grain viability of Pisum sativum L cv. Pleven 4. The effect of their application was high and exceeded data for the untreated control (44.2 and 47.23 % regarding pollen germination and pollen tube elongation, respectively), as well as the effect of the control organic algal fertilizer Biofa (17.5 and 27.9 %, respectively). Pollen grains were inoculated in four culture media. A medium containing 15% sucrose and 1% agar had the most stimulating impact on pea pollen grains. Pollen viability, evaluated by staining with 1% carmine, was within limits of 74.72-87.97%. The highest viability of pollen grains was demonstrated after the application of Nagro organic nano-fertlizer.